2020
DOI: 10.1161/strokeaha.120.030105
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Stroke Onset to Hospital Arrival Time During COVID-19

Abstract: Background and Purpose: The current coronavirus disease 2019 (COVID-19) pandemic represents a global public health crisis, disrupting emergency healthcare services. We determined whether COVID-19 has resulted in delays in stroke presentation and affected the delivery of acute stroke services in a comprehensive stroke center in Hong Kong. Methods: We retrospectively reviewed all patients with transient ischemic attack and stroke admitted via the acute st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
219
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(241 citation statements)
references
References 8 publications
14
219
6
2
Order By: Relevance
“…Another study showed similar results with a significant increase in LKWT to door time during the COVID-19 period, and more importantly a significant reduction in patients who arrived within the 4.5 hour tPA window [ 2 ]. Similarly, Kerleroux et al also found that patients who were treated during the same time period were less likely to receive tPA [ 3 ].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Another study showed similar results with a significant increase in LKWT to door time during the COVID-19 period, and more importantly a significant reduction in patients who arrived within the 4.5 hour tPA window [ 2 ]. Similarly, Kerleroux et al also found that patients who were treated during the same time period were less likely to receive tPA [ 3 ].…”
Section: Discussionmentioning
confidence: 72%
“…In addition to its effect on the economy, SARS2-CoV-2 also caused major disruptions in healthcare as many hospitals were forced to cancel elective surgeries and postpone outpatient and specialty appointments to conserve personal protective equipment (PPE) and reduce exposure risk. Teo et al has suggested that the recent change in healthcare has had a significant impact on care of stroke patients [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for this fact might be that not the incidence of certain diseases decreased during that time, but patients were afraid of infection and avoided attending hospitals for further diagnosis and treatment [10]. Furthermore, reports from Spain and Hong Kong showed that in the case of a cerebral stroke, not only was the number of treated cases reduced but also the arrival time and start of treatment was delayed [12,13].…”
Section: Introductionmentioning
confidence: 99%